Synthesis and Spectroscopic Study of 3-Hydroxy-2-(3-(4-Nitrobenzoyl) Thiouriedo) Propanoic Acid with their Metal Complexes - Abbas M. Abbas (Journal of Global Pharma Technology, 2016)
A new ligand 3-hydroxy-2-(3-(4-nitrobenzoyl) thiouriedo) propanoic acid (NTP) where synthesized by reaction of 4-nitro benzoyl isothiocyanate with serine amino acid. The ligand was characterized by FT-IR, NMR spectra and the elemental analysis. The transition metal complexes of this ligand where synthesize and characterized by UV-Visible spectra, FT-IR, magnetic suscpility, conductively measurement, The general formula [M (NTP) 2] where M+2= (Mn, Co, Ni, Cu, Zn, Cd, Hg,), the form of molecular for these complexes as tetrahedral except Cu has square planer.Keywords: Serine, 4-nitrobenzoyl isothiocyanate, Transition metals.